Efektivitas Pembelajaran Tematik Integratif Kelas 1 di Sekolah Dasar Negeri Kranggot Kota Cilegon - Ifa Elfiyanti; Desty Endrawati Subroto; Frailani Magfiroh; Dewi Hanifah Zauharun Nafsah Billa Anggrini; Teguh Nurhadi Mugni (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The purpose of this study is to present the concept and implementation of integrative theme learning in the first grade at Kranggot Elementary School. To provide students with meaningful experiences, integrative theme learning combines various skills from various fields and topics. After being given educational materials, the goal is to help students become more proficient in observing, asking questions, reasoning, and presenting what they have learned. Learning objects intersect with artistic, cultural, social, and natural events. Learning efforts that are focused on the developmental stage of elementary school kids, who still view the world holistically and are only able to understand the relationship between ideas fundamentally, namely integrative theme learning. Therefore, students are expected to have much better abilities in attitudes, skills, and knowledge through this integrative theme approach.